1985
DOI: 10.1139/e85-205
|View full text |Cite
|
Sign up to set email alerts
|

Uranium uptake by algae: experimental and natural environments

Abstract: Monocultures of the freshwater green algae Ankistrodesmus sp. grown at pH 8.1–8.2 and 13–16 °C, in solutions containing 2 ppm U chelated with EDTA, acquired 1000 – 10 000 ppm uranium by dry weight. In some algae, a uranium mineral of cubic habit was detected. At Elliot Lake, Ontario, Euglena sp. thriving in tailings discharge contain on average 184 ppm U. Tailings waters contain high concentrations of dissolved uranium, on average 273 ppb. In natural drainage waters, above and below tailings, dissolved U avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…There has been some work published on the effects of U on algal species suspended in the water column (Charles et al, 2002;Franklin et al, 2000;Hogan et al, 2005;Mann and Fyfe, 1985) but less so on the effects of anthropogenic U contamination on densely packed and highly structured periphyton communities. Determining the effects of contaminants on whole communities ismore complicated than using single species, but the effort provides a more realistic picture of the impact of a stressor or contaminant on a complex natural system (Cairns et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…There has been some work published on the effects of U on algal species suspended in the water column (Charles et al, 2002;Franklin et al, 2000;Hogan et al, 2005;Mann and Fyfe, 1985) but less so on the effects of anthropogenic U contamination on densely packed and highly structured periphyton communities. Determining the effects of contaminants on whole communities ismore complicated than using single species, but the effort provides a more realistic picture of the impact of a stressor or contaminant on a complex natural system (Cairns et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Trenfield et al [21] studied the influence of dissolved organic carbon on uranium toxicity to Euglena gracilis at pH 6. Both groups [19,21], however, did not provide any information on the respective uranium speciation in the surrounding water and associated with Euglena cells.…”
Section: Introductionmentioning
confidence: 93%
“…with uranium are, however, so far very limited. In two studies [19,20] a significant accumulation of uranium by unspecified Euglena sp. cells thriving in tailings at the Elliot Lake (Ontario) were observed and from this it was concluded that specific algae must be important in the transfer of uranium from the hydrosphere to the sediments.…”
Section: Introductionmentioning
confidence: 99%
“…Average concentrations of U were likely highest during drier periods when spring water (i.e., groundwater) contributions were proportionally greater. Dissolved U in the lake was subject to additional variability caused by the abundance of suspended algae with probable high affinity for U. Algae have been shown to concentrate U by as much as 1000-10,000X compared to coexisting water (Degens et al, 1979;Mann and Fyfe, 1984;Dienemann et al, 2002). Algal remains settled to the lake bottom and were incorporated into silt and clay lake sediments, forming gyttja.…”
Section: Uranium Uptake In Lakebed Sedimentsmentioning
confidence: 99%